CHALLENGES OF LOCALIZATION OF THE POLICY FRAMEWORK AND NATIONAL ACTION PLAN FOR PREVENTING VIOLENT EXTREMISM IN PLATEAU STATE, NIGERIA - BEJI GOWAL BEKUMA; JOHN UKAWUILULU (International Studies Journal)
The study examines the challenges of localization of the policy framework and national action plan for preventing violent extremism in Plateau state. The paper noted that violent extremism is fundamentally, repudiations of democratic values of tolerance, respect, inclusion and diversity. In Nigeria, threats from violent extremism are targeted against individuals, groups and the state. These threats have gravely undermined economic development, social progress, political stability, national and human security, and peaceful coexistence in the country. The theoretical framework for this study is the Context, Input, Process, Product (CIPP) Evaluation Model. Questionnaires and in-depth interview were used to collect the data for this study. Simple descriptive statistics presented in tables using frequency and percentages were used to analyse the quantitative data collected in the study. While, in-depth interview summaries were used to analyse the qualitative data. The Findings show that: the policy framework and national action plan for preventing violent extremism is a product that went through several processes and stakeholders. But essentially, it contains a strategic vision Nigeria holds for preventing violent extremism, which is a product of research, global practices and knowledge of the root causes of violent extremism. There is low awareness of the level of localization and implementation of the policy framework and national action plan for preventing violent extremism in Plateau state. The challenges of the localizing and implementing the policy framework and national action plan for preventing violent extremism in Plateau state are largely due to lack of coordination, lack of awareness, lack of effectiveness, trust gap between government and citizens. The paper recommended that: effective national coordination is urgently needed to localize the policy at the grassroots. While, different civil society organizations should not work at cross-purposes but be coordinated in their activities toward preventing violent extremism in Plateau State.